Bordetella pertussis population dynamics and phylogeny in Japan after adoption of acellular pertussis vaccines. Issue 5 (17th May 2018) - Zomer, Aldert; Otsuka, Nao; Hiramatsu, Yukihiro; Kamachi, Kazunari; Nishimura, Naoko; Ozaki, Takao; Poolman, Jan; Geurtsen, Jeroen
Abstract : Bordetella pertussis, the causative agent of whooping cough, has experienced a resurgence in the past 15 years, despite the existence of both whole-cell and acellular vaccines. Here, we performed whole genome sequencing analysis of 149 clinical strains, provided by the National Institute of Infectious Diseases (NIID), Japan, isolated in 1982–2014, after Japan became the first country to adopt acellular vaccines against B. pertussis . Additionally, we sequenced 39 strains provided by the Konan Kosei Hospital in Aichi prefecture, Japan, isolated in 2008–2013. The genome sequences afforded insight into B. pertussis genome variability and population dynamics in Japan, and revealed that the B. pertussis population in Japan was characterized by two major clades that divided more than 40 years ago. The pertactin gene was disrupted in about 20 % of the 149 NIID isolates, by either a deletion within the signal sequence (ΔSS) or the insertion of IS element IS 481 ( prn  :: IS 481 ). Phylogeny suggests that the parent clones for these isolates originated in Japan. Divergence dating traced the first generation of the pertactin-deficient mutants in Japan to around 1990, and indicated that strains containing the alternative pertactin allele prn2 may have appeared in Japan around 1974. Molecular clock data suggested that observed fluctuations in B. pertussis population size may have coincided with changes in vaccine usage in the country. The continuing failure to eradicate the disease warrants an exploration of novel vaccine compositions.